Pengembangan Multimedia Pembelajaran Interaktif Berbasis Video Mata Pelajaran Pendidikan Agama Islam untuk Meningkatkan Minat Belajar Siswa - Rachmawati, Ifa; Kusmiyati, Kusmiyati (Edusia: Jurnal Ilmiah Pendidikan Asia, 2023)
This research aims to produce an interactive multimedia that is suitable for Islamic religious education learning activities with commendable properties and ablution. In this study, it was developed using the ADDIE research model (Analyze, Design, Development, Implementation, Evaluation). The data collected are qualitative and quantitative data using several data collection methods, including: observation method, interview method, and questionnaire method. The results showed (1) Design the development of interactive learning multimedia. The steps taken are: (a) analyzing needs, (b) design, (c) development and implementation, valid with the results of subject expert reviews with very good qualifications 96.22%, the results of learning media expert reviews are very good 98%, the results of learning media expert reviews are very good 95%, individual trial results with good qualifications are 94%. The results of small group trials with excellent qualifications are 95.55%. Based on the validation test, the development of interactive learning multimedia shows effective results, so it is suitable for use in the process of learning activities.